Protocol and statistical analysis plan for the REstricted fluid therapy VERsus Standard trEatment in Acute Kidney Injury—REVERSE‐AKI randomized controlled pilot trial. Issue 6 (26th February 2020) - Vaara, Suvi T.; Ostermann, Marlies; Selander, Tuomas; Bitker, Laurent; Schneider, Antoine; Poli, Elettra; Hoste, Eric; Joannidis, Michael; Zarbock, Alexander; van Haren, Frank; Prowle, John; Pettilä, Ville; et al.
Abstract : Background: Fluid accumulation frequently coexists with acute kidney injury (AKI) and is associated with increased risk for AKI progression and mortality. Among septic shock patients, restricted use of resuscitation fluid has been reported to reduce the risk of worsening of AKI. Restrictive fluid therapy, however, has not been studied in the setting of established AKI. Here, we present the protocol and statistical analysis plan of the REstricted fluid therapy VERsus Standard trEatment in Acute Kidney Injury—the REVERSE‐AKI trial that compares a restrictive fluid therapy regimen to standard therapy in critically ill patients with AKI. Methods: REVERSE‐AKI is an investigator‐initiated, multinational, open‐label, randomized, controlled, feasibility pilot trial conducted in seven ICUs in five countries. We aim to randomize 100 critically ill patients with AKI to a restrictive fluid treatment regimen vs standard management. In the restrictive fluid therapy regimen, the daily fluid balance target is neutral or negative. The primary outcome is the cumulative fluid balance assessed after 72 hours from randomization. Secondary outcomes include safety, feasibility, duration, and severity of AKI, and outcome at 90 days (mortality and dialysis dependence). Conclusions: This is the first multinational trial investigating the feasibility and safety of a restrictive fluid therapy regimen in critically ill patients with AKI. Trial registration: clinical.trials.gov NCT03251131.